Drivers of store brand usage in an Asian emerging market: evidence from Vietnam. Issue 12 (14th December 2015) - Diallo, Mbaye Fall
Abstract : Purpose: – Although they are increasingly offered by mass retailers in Asia, store brands (SBs) are not well understood in Asian countries. The purpose of this paper is to investigate how store and brand-level factors affect consumer usage of SBs in an Asian emerging country. Design/methodology/approach: – A consumer survey, based on sample of 445 respondents, is undertaken in two competing modern retail chains in Vietnam. Structural equation modelling is used to test the research hypotheses. A latent interaction variable was created to test the moderation of store familiarity. Findings: – Results indicate that SB price image, consumer attitude towards SBs and SB perceived value influence most strongly SB usage in Vietnam, whereas store image perceptions have no direct effect on it. Some investigated relationships differ across store formats. Overall, store familiarity has a weak direct effect on SB usage, but its interaction effects differ depending on store format. Research limitations/implications: – The study is limited because it investigated only one Asian country and two retail chains. Besides, it did not account for effect of product categories on SB usage. Practical implications: – Findings indicate that a positive store image is not sufficient to increase consumer usage of SBs in Vietnam. Retailers should be especially careful when designing retail outlets in this market, where consumers seem attached to traditions. Results highlight the importance of taking measures to develop more positive attitudes towards SBs. Also, store familiarity has a weak effect on SB purchase and should therefore be monitored more carefully by retail chains operating in Vietnam. Originality/value: – This research is the first to address Vietnamese consumer usage of SBs. In contrast to their counterparts in other emerging countries, Vietnamese consumers do not strongly rely on store image when purchasing SBs. Their focus is rather on brand perceived value. These results challenge conventional wisdom that attributes a low utilitarian value orientation to Asian consumers.